GAMBARAN FAKTOR RISIKO IBU HAMIL RISIKO TINGGI - S, Nurlita Agnis; Sujiyatini, Sujiyatini; Arum, Dyah Noviawati Setya (Jurnal Kesehatan Ibu dan Anak, 2015)
Maternal Mortality Rate (MMR) in Indonesia rose to 359 / 100,000 live births. Greater maternal deaths occur in women who alreadyhave risk factors for pregnant womenwith high risk because of risk factors can lead to complications in pregnancy may be a cause ofmaternal death. Bantul District is a district with a high percentage of pregnant women the highest risk (26.92%). PanembahanSenopati Bantul Hospitalmaternalmortality is 1 in February 2014 due to cases ofPEBand atonic uterus.This study aims to describerisk factors for high-risk pregnant women in hospitals Panembahan Senopati Bantul in February 2014. The study was conductedwith descriptive research method with cross sectional study design. The subjects were all pregnant women a high risk,namely apregnant women who have been diagnosed by a physician as a high-risk pregnant women who visited in Panembahan SenopatiBantul Hospital in February 2014. There are 143 womenwith high-risk pregnant women inwhich each had more than one risk factorin a group of risk factors. Results of the study of risk factors of high risk pregnant women in hospitals Panembahan Senopati Bantulon month in February 2014 that the first group of risk factors or distress Obstetric There Highest Potential risk factors grande multi,old primi secondary, age ?35 years, a history of SC; risk factor group II There is a majority or distressObetetri on risk factors anemia,KPD, PER, and was found pregnant women with PMS; the third group of risk factors or There Emergency Obstetric most at riskfactors for severe preeclampsia or eclampsia.